CITIZEN LAWSUIT (GUGATAN WARGA NEGARA) TERHADAP PENYELENGGARA NEGARA DALAM MENCARI KEADILAN - Julaiddin, Julaiddin; Sari, Henny Puspita (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
To fight for human interests in seeking justice, environmental law provides a route toresolve problems that harmonize the economic and social interests of Citizen Lawsuit.Citizen Lawsuit is essentially a mechanism for citizens to sue state officials liable fornegligence in fulfilling the rights of citizens. Therefore, on the basis of his negligence, inthe petitum of the lawsuit, the state was punished for issuing a regulation (regeling) so thatthe negligence did not occur again in the future.